From Seeds to Cell: Improving PEMFC Performance and Durability by Seed‐Mediation Synthesis for PtNiIr ORR Nanocatalysts - Lujin Pan; Thomas Merzdorf; Carlos A. Campos‐Roldàn; An Guo; Jiasheng Lu; Johannes Schmidt; Marc Heggen; Malte Klingenhof; Xingli Wang; Sebastian Möhle; Sören Selve; Deborah Jones; et al. (Advanced Science)
Abstract Proton exchange membrane fuel cells (PEMFCs) provide efficient, green power solutions. However, the sluggish kinetics of the oxygen reduction reaction (ORR) at the cathode, with its need for elevated Pt loadings, lowers efficiency and raises cost, which hinders their wider implementation. Pt‐based designer alloy electrocatalysts, more specifically ternary PtNiX nanocatalysts, hold great potential for improving ORR activity and thus overall cell performance. This study explores synthesis and performance evaluations of novel ternary PtNiIr ORR catalysts prepared using seed‐mediation at different catalyst loadings and deposited on various carbon support materials. Membrane electrode assembly (MEA) performance evaluations are carried out to assess catalyst activity and stability under operating conditions, revealing better performance and durability for seed‐mediated catalysts compared to the non‐seed‐mediated catalyst used as a reference. The results showed further improved performance and durability of the seed‐mediated catalysts on porous carbon than solid carbon, due to the deposition of catalyst nanoparticles inside the carbon pores. Degradation analysis using online inductively coupled plasma – mass spectrometry (ICP‐MS) indicated the dissolution of metals during contact with the electrolyte and under operating conditions, confirming the observed catalyst stability trends in MEA. The experiments highlighted the impact of catalyst composition and supports on the stability of the materials.